Antimicrobial and self‐crosslinking potential of experimentally developed dioctadecyldimethyl ammonium bromide and riboflavin dentin adhesive. Issue 11 (21st May 2021) - Daood, Umer; Malik, Ammar Abdullah; Ilyas, Muhammad Sharjeel; Ahmed, Asrar; Qasim, Syed Saad B.; Banavar, Spoorthi Ravi; Khan, Abdul Samad; Kuan, Esther Kok Sook; Bilal, Sobia; Matinlinna, Jukka; Seow, Liang Lin
Abstract: The aim of the study is to investigate a new formulation, based on dioctadecyldimethyl ammonium‐bromide (QA) and riboflavin (RF), combining antimicrobial activities and protease inhibitory properties with collagen crosslinking without interference to bonding capabilities in a rabbit model. Quaternary ammonium riboflavin (QARF) experimental adhesives modified with dioctadecyldimethyl ammonium‐bromide and riboflavin were bonded (0.5/1.0/2.0%) to rabbit dentin to investigate for pulpal‐histology, interfacial‐morphology, transmission electron microscopy, mechanical properties, collagen crosslinking, micro‐Raman analysis, antimicrobial, and anti‐protease activities. Collagen type‐I molecules were generated using molecular‐docking. Odontoblasts appeared with normal histology, were seen in controls with no inflammatory cells detected in 0.5% specimens at day 7 and mild inflammatory response at day 30. In QARF 2.0%, inflammatory cells were not detected at day 7 and 30 (p < .05). Dentinal tubules are seen with intact collagen surface in 1% specimens. Resin penetrated inside 1% adhesive specimens with few irregularly funnel‐shaped tags. Transmission electron microscopy showed thinner collagen in all specimens except 1% QARF specimens. Biofilms were influenced by QARF adhesives. Elastic moduli were significantly higher in 1.0% and 2.0% QARF adhesive specimens with a significant increase in total crosslinks. Stable amide groups with anti‐protease activity was observed in QARF groups. Charged residues were seen in the triple helix hCOL3A1, Gly489‐Gly510 after stabilisation with formulation. The 1% QARF modified adhesives improved biochemical and biomechanical properties of rabbit dentin.